Malay language as a mediator for idea generation among students in English language group activity / Noor 'Izzati Ahmad Shafiai - Ahmad Shafiai, Noor 'Izzati (2021)
Students' participation in discussions encourages idea exploration. However, it is challenging for low-proficient students to participate in an English language (L2) classroom. Using Sociocultural Theory as theoretical framework, this qualitative paper aims to explore how students with low English proficiency utilize Malay language (L1) as a mediator for idea generation in a discussion. Three low-proficient students and three students of mixed proficiency were given a one-hour English writing task. The study revealed that Malay language functioned as a mediator when the students presumed that by speaking in Malay, it may ease their speech production as well as message delivery. The outcome of this study does not only provide initial insights to low-proficient learners' option in getting their English tasks done, but also allows English instructors to reconsider strict restriction of the use of Malay in English learning